Role of pRIFLE and AKIN Criteria for Diagnosis of Neonatal Acute Kidney Injury in a Special Care Baby Unit (SCABU) (Bangladesh Journal of Child Health, 2018)
Background: The present study was intended to make a comparison of acute kidney injury (AKI) diagnosed and classified by two diagnostic modalities such as paediatric Risk Injury Failure Loss of End Stage Renal Failure (pRIFLE ) criteria and acute kidney injury network (AKIN) staging .Methodology: A total 44 neonates (from 3 – 28 days) with AKI as case and other 26 neonates without AKI as control were also included in the study. Both were admitted in special care baby unit (SCABU) Dhaka Medical College Hospital.Results: The neonate of ≤7 days old comprised the main bulk. Majority of the neonates were of average birth weight. The diagnosis was based on estimated creatinine clearance (eCCL) criteria of pRIFLE showed that 40.9% neonates were at risk of AKI, 20.5% have had already injured. Higher proportions of neonates were classified as failure (38.6%).The diagnosis was based on Serum creatinine criteria of AKIN showed that about 64% of the neonates were at AKI-stage I, 22.7% at stage-II and 13.6% at stage-III. Higher proportions of neonates were classified as stageI.We found moderate agreement between pRIFLE criteria and AKIN staging, these two diagnostic modalities for diagnosis of AKI by kappa- statistics. Outcome of neonatal AKI predicted by pRIFLE criteria was significantly higher compared to AKIN staging (p < 0.001) in respect to SCABU stay, multiorgan failure, need for dialysis. Here 43% neonates with AKI were improved with normal renal function and 16% improved with impaired renal function. Increased frequency of death (34%) in this series was due to multiorgan involvement with acute kidney failure (AKF). Mortality was significantly higher (p=0.03) in failure group by pRIFLE criteria compared to AKIN stage III. So it is evident that pRIFLE criterions are highly sensitive to classify AKI, it is also superior to AKIN staging in predicting early diagnosis, need for intervention and immediate outcome.Conclusion: The study concluded that pRIFLE criteria and AKIN staging are useful in the diagnosis of AKI in neonates and pRIFLE criteria are fairly sensitive for better characterization of AKI.Bangladesh J Child Health 2017; VOL 41 (3) :147-154